AUTOC-AR: A Car Design and Specification as a Work Safety Guide Based on Augmented Reality Technology - Aulia Akhrian Syahidi; Subandi Subandi; Amran Mohamed (Jurnal Pendidikan Teknologi dan Kejuruan, 2020)
The development of Augmented Reality (AR) technology until now continues to increase. Utilization of AR has been used in various aspects of life, including aspects of education, is no exception for automotive engineering education. In recent years, a variety of ideas and the latest innovations about automotive by utilizing AR technology began to boom, especially in the area of car design aimed at car production companies. At the car production stage, human resources skilled in understanding the design and specifications of car features are required. The seeds of educated human resources start from vocational students in automotive engineering expertise programs. This study aims to develop and implement an application called AUTOC-AR that functions to help and facilitate students in learning automotive engineering skills in vocational schools and supporting safety in the workplace. The research methodology consisted of a literature review and excavation of problems and needs, solution recommendations, application development, testing, results and discussion, conclusions and future work. The Extreme Programming (XP) model was used as a development method. Marker-based tracking was used as a detection approach. As many as 25 students as end-users were involved to use AUTOC-AR. The result is that all features in the AUTOC-AR application function properly based on the expected specifications. Non-functional testing has been carried out by adopting a user experience approach with a final average value of 4.83 with a percentage of 96.6%.